Pivotal or peripheral - Sitty, Jean-Pierre Gabriel (2024)
This research investigates the extent to which generative artificial intelligence (GAI) accelerates early-stage startups, focusing on the area ‘ideation’. By integrating literature and expert interviews, the study aims to fill the current research gap. This research examines how GAI affects the success of startups, by mitigating common failure factors and capitalizing on success factors. The results show that GAI varies between different kind of tasks and offers practical recommendations and ideas for future research. These insights guide founders in effectively utilizing GAI to navigate the new era of GAI-enhanced entrepreneurship.